2017
DOI: 10.1097/rmr.0000000000000133
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging for the Evaluation of Pulmonary Embolism

Abstract: Pulmonary embolism (PE) is a leading cause of acute cardiovascular death throughout the world. Although computed tomography angiography (CTA) is the primary imaging study used to diagnose acute PE, pulmonary magnetic resonance angiography (MRA) is increasingly being used in patients with contraindications for CTA. This manuscript reviews the MRA techniques used for the diagnosis of PE and discuss how these techniques can be implemented in routine clinical practice. In addition, the efficacy and effectiveness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…The main difference in interpreting MRI compared to CTPA is the artefacts. (60,63) In CTEPH the expected MRI findings are also similar to those seen on CTPA. An early study by Ley et al from 2003 showed that MRI is equal to CTPA on segmental level, but CTPA was superior on the subsegmental level and for evaluating intraluminal webs and thrombotic wall thickening (55).…”
Section: Magnetic Resonance Imagingsupporting
confidence: 52%
See 2 more Smart Citations
“…The main difference in interpreting MRI compared to CTPA is the artefacts. (60,63) In CTEPH the expected MRI findings are also similar to those seen on CTPA. An early study by Ley et al from 2003 showed that MRI is equal to CTPA on segmental level, but CTPA was superior on the subsegmental level and for evaluating intraluminal webs and thrombotic wall thickening (55).…”
Section: Magnetic Resonance Imagingsupporting
confidence: 52%
“…Nevertheless, CT has a higher sensitivity on the subsegmental level, in the detection of intraluminal webs and thrombotic wall thickening (55). In summary, the utility of MRI for diagnosing CTEPH has not been established as yet (63).…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…The routine protocol includes static steady-state free precession (SSFP) sequences, contrast-enhanced 3 D magnetic resonance angiography (MRA) using a T1-weighted gradient-echo (GRE) sequence, and a 2 D axial or 3 D T1-weighted GRE sequence post-contrast. If the patient tolerates the flat positioning in the MRI scanner well, an additional time-resolved, contrast-enhanced 3 D (i. e. 4 D) MRA prior to the 3 D MRA sequence is helpful to obtain dynamic perfusion information [14].…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Contrast-enhanced 3 D MRA with high spatial resolution is obtained in coronal orientation during three inspiratory breath-holds for acquisition of pre-contrast images for subtraction purposes, arterial phase images and late arterial phase images (▶ Fig. 2) [14]. 0.1 mmol/kg gadolinium-based contrast agent is administered at a flow rate of 2 ml/s.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%